Ectopic osteogenesis with immortalized human bone marrow stromal stem cells and heterologous bone - Teng, Yong; Hu, Yunyu; Li, Xusheng; Guan, Yucheng; Gui, Junhao (Journal of Applied Biomedicine, 2011)
To resolve the problem of the insufficient availability of seed cells and to provide seed cells for tissue engineering research, an immortalized human bone marrow stromal stem cell line (MSCxj cells) was established in our department to investigate the ectopic osteogenesis of MSCxj cells. MSCxjs were grown with a heterogeneous bone scaffold for 48 h. Three groups were included: A: MSCxjs of 35 PDs were maintained with heterogeneous bone; B: MSCxjs of 128 PDs were maintained with heterogeneous bone; and C: heterogeneous bone alone. Tetracycline fluorescence staining, H&E staining, and ponceau staining, immunohistochemistry and bone histomorphometry were performed. At the same time, scanning electron microscopy was conducted to detect the growth of MSCxjs and heterogeneous bone. Scanning electron microscopy showed favorable adherence of MSCxjs to heterogeneous bone. A large number of newly generated filamentous extracellular matrix and fine granular materials were found to cover the cells. The results from staining showed that the osteogenesis was not obvious in group A/B 4 weeks after transplantation. Eight weeks after implantation, osteoid matrix deposition was noted in and around the heterogeneous bone in group A/B. Twelve weeks after implantation, osteogenesis was increased in group A/B. There were no significant differences in the time course for bone formation and the amount of newly generated bone between group A/B. Like primary hBMSCs, MSCxj cells have favourable ectopic osteogenesis and can be applied as seeded cells in bone tissue engineering.
Keywords: Statistics as Topic; techniky tkáňových kultur; Stem Cells; statistika jako téma; osteogeneze; experimenty na zvířatech; tkáňové inženýrství; lidé; Bone Marrow; Animal Experimentation; Mice; kmenové buňky; transplantace heterologní; Transplantation, Heterologous; myši; Tissue Culture Techniques; kostní dřeň; Tissue Engineering; Osteogenesis; Humans